Using task-based instruction in an ESP course in the Computer Center at the University of Costa Rica = El uso de la Metodología Basada en Tareas en un curso de inglés con propósitos específicos en el Centro de Informática de la Universidad de Costa Rica - Córdoba Cubillo, Patricia María 1954-
This article presents the advantages of using Task-based Learning to help learners from the Computer Center at the University of Costa Rica infer the rule of the superlative form of adjectives in English. This group of learners was taking an ESP course that was team taught by two instructors. The course lasted four months, and the instructors covered four different units. It is important to mention that the methodology based on tasks help learners pay more attention or concentrate more on meaning than Task-based language learning is an approach in which learners concentrate more on meaning than on form. By doing this, students perform different communicative tasks, which happen to be more meaningful because they are close to the learners' reality, instead of doing form-based discrete exercises, which are usually decontextualized and meaningless because they do not see a reason to do them. In the lesson presented in this article, the Computer Center students were asked to express their own ideas, either orally or in a written mode, about the topic of the lesson, the superlative form of the adjectives in English.